Tales, tunes, and tassa drums : retention and invention in Indo-Caribbean music - Manuel, Peter, 1952- (University of Illinois Press, 2015)
"Today's popular tassa drumming emerged from the fragments of transplanted Indian music traditions half-forgotten and creatively recombined, rearticulated, and elaborated into a dynamic musical genre. A uniquely Indo-Trinidadian form, tassa drumming invites exploration of how the distinctive nature of the Indian diaspora and its relationship to its ancestral homeland influenced Indo-Caribbean music culture. Music scholar Peter Manuel traces the roots of neotraditional music genres like tassa drumming to North India and reveals the ways these genres represent survivals, departures, or innovative elaborations of transplanted music forms. Drawing on ethnographic work and a rich archive of field recordings, he contemplates the music carried to Trinidad by Bhojpuri-speaking and other immigrants, including forms that died out in India but continued to thrive in the Caribbean. His reassessment of ideas of creolization, retention, and cultural survival defies suggestions that the diaspora experience inevitably leads to the loss of the original culture, while also providing avenues to broader applications for work being done in other ethnic contexts"--